3D-printed titanium implant combined with interleukin 4 regulates ordered macrophage polarization to promote bone regeneration and angiogenesis. Issue 7 (1st July 2021) - Zhao, Da-Wang; Ren, Bing; Wang, Hong-Wei; Zhang, Xiao; Yu, Ming-Zhi; Cheng, Lei; Sang, Yuan-Hua; Cao, Shuai-Shuai; Thieringer, Florian M.; Zhang, Dong; Wan, Yi; Liu, Chao
Abstract : Aims: The use of 3D-printed titanium implant (DT) can effectively guide bone regeneration. DT triggers a continuous host immune reaction, including macrophage type 1 polarization, that resists osseointegration. Interleukin 4 (IL4) is a specific cytokine modulating osteogenic capability that switches macrophage polarization type 1 to type 2, and this switch favours bone regeneration. Methods: IL4 at concentrations of 0, 30, and 100 ng/ml was used at day 3 to create a biomimetic environment for bone marrow mesenchymal stromal cell (BMMSC) osteogenesis and macrophage polarization on the DT. The osteogenic and immune responses of BMMSCs and macrophages were evaluated respectively. Results: DT plus 30 ng/ml of IL4 (DT + 30 IL4) from day 3 to day 7 significantly (p < 0.01) enhanced macrophage type 2 polarization and BMMSC osteogenesis compared with the other groups. Local injection of IL4 enhanced new bone formation surrounding the DT. Conclusion: DT + 30 IL4 may switch macrophage polarization at the appropriate timepoints to promote bone regeneration. Cite this article: Bone Joint Res  2021;10(7):411–424.